The stabilisation of low-fat mayonnaise by whey protein isolate-microbial exopolysaccharides (Weissella confusa W-16 strain) complex - Yalmanci, Dilara; Dertli, Enes; Tekin-Cakmak, Zeynep Hazal; Karasu, Salih (WILEY, 2023)
This study aims to evaluate the fat-substituting feature of the complex of whey protein isolate (WPI) and dextran structure exopolysaccharide (EPS) synthesised by Weissella confusa JCM 1093 strains in mayonnaise samples. The flow behaviour, frequency sweep and three interval thixotropy test properties of the samples were compared with the control groups. Thermal loop test was applied to determine the emulsion stability of the samples. Oxidative stability was tested with OXITEST, and induction period values were compared. K values of the samples varied between 20.05 and 169.13 Pa.s(n) and the n values vary between 0.133 and 0.383. Samples showed pseudoplastic behaviour (n < 1). G' of all samples is greater than G, meaning that all samples showed a solid-like behaviour like conventional mayonnaise. The complex of 2% EPS and 5% WPI provided a solid structure and improved the physical stability of low-fat mayonnaise. The results showed that the samples had high physical stability when they experienced thermal stress at low and high temperatures. As a result, the WPI and EPS complex can be used as a fat replacer for improving the rheological properties, emulsion and oxidative stability in low-fat mayonnaise samples.
Keywords: Emulsion stability; exopolysaccharide; fat substitutes; microbial polysaccharides; LIPID OXIDATION; ANTIOXIDANT ACTIVITY; OIL; BIOACTIVITY; SOURDOUGH; EMULSION; BACTERIA; FRACTION; CASEIN; FLOW; Food Science & Technology